Leaving Family to Return to Family: Roots Migration Among Second‐Generation Italian‐Australians. (September 2017) - Sala, Emanuela; Baldassar, Loretta
Abstract: This article examines "roots migration" (visits and repatriations) of second‐generation Italian‐Australians to their ancestral homeland. Despite the current economic climate, these young adults have moved to Italy, hence their motivation for migration goes beyond economic drivers and is best explained by psychosocial factors. Drawing on ethnographic analysis, our aim is to highlight the importance of the dimension of the family, which has tended to be implicitly rather than explicitly studied, within the transnational social field and imaginary. Family is a somewhat contradictory factor that generates ties to the ancestral homeland, leading us to apply a psychosocial approach comprising an analysis of affective and relational dimensions through the lens of familial habitus . Our findings highlight how family is the major motivation for roots migration involving an interconnected process of moving away from (the migrant) family and of moving to (the homeland) family as a culturally appropriate way of gaining independence.